Superficial and Deep Foveal Avascular Zone Area Measurement in Healthy Subjects Using Two Different Spectral Domain Optical Coherence Tomography Angiography Devices - Anvari, Pasha (J Ophthalmic Vis Res, 2020)
PURPOSE: To compare the area of the foveal avascular zone (FAZ) in the superficial and deep retinal layers using two different spectral-domain optical coherence tomography angiography (OCTA) devices. METHODS: A cross-sectional comparative study was conducted to obtain macular OCTA images from healthy subjects using Optovue RTVue XR Avanti (Optovue, Inc, Fremont, CA) and Spectralis HRA+OCTA (Heidelberg Engineering, Heidelberg, Germany). Two independent trained graders measured the FAZ area using automated slab segmentation. The FAZ area in the superficial and deep retinal layers were compared. RESULTS: Twenty-three eyes of 23 subjects were included. The graders agreement was excellent ([Formula: see text] 0.86) for all measurements. The mean FAZ area was significantly larger at the superficial retinal layer as compared to the deep retinal layer on both devices (0.31 [Formula: see text] 0.08 mm [Formula: see text] vs 0.26 [Formula: see text] 0.08 mm [Formula: see text] in Optovue and 0.55 [Formula: see text] 0.16 mm [Formula: see text] vs 0.36 [Formula: see text] 0.13 mm [Formula: see text] in Spectralis, both P [Formula: see text] 0.001). The mean FAZ area was significantly greater in the superficial and deep retinal layers using Spectralis as compared to Optovue measurements (P [Formula: see text] 0.001 for both comparisons). CONCLUSION: In contrast to previous reports, the FAZ area was larger in the superficial retina as compared to deep retinal layers using updated software versions. Measurements from different devices cannot be used interchangeably.